Hubungan Pengetahuan, Sikap, dan Dukungan Keluarga dengan Kepatuhan Perawatan Kaki Pasien Diabetes Melitus Tipe 2 di Puskesmas Halmahera - Tri Setiyo Budi; Dwi Yogo Budi Prabowo; Hanifah Sahar Al Afra (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Diabetes Mellitus (DM) is a chronic disease characterized by elevated blood glucose levels resulting from disturbances in carbohydrate, fat, and protein metabolism. This study determined the correlation among knowledge, attitudes, family support, and adherence to foot care among patients with Type 2 Diabetes Mellitus at Halmahera Community Health Center. This quantitative study employed a cross-sectional design involving 78 respondents. The researchers used the Diabetic Foot Knowledge Scale (DFKS) to measure knowledge, the Diabetic Foot Behavior Checklist (DFBC) to assess foot care adherence, the Hensarling Diabetes Family Support Scale (HDFSS) to evaluate family support, and an attitude questionnaire to measure respondents' attitudes. The results showed that most respondents were older than 65 years (56.4%), female (52 respondents; 66.7%), had completed elementary school as their highest level of education (35 respondents; 44.9%), were unemployed (59 respondents; 75.6%), and had lived with diabetes for a prolonged period (37 respondents; 47.4%). Spearman’s rank correlation test revealed a significant positive relationship between knowledge and adherence to foot care (p = 0.000; r = 0.743), indicating a strong correlation. The test also showed a significant positive relationship between attitude and adherence to foot care (p = 0.001; r = 0.377), although the correlation was weak. In addition, family support was significantly and positively associated with adherence to foot care (p = 0.000; r = 0.499), with a moderate correlation strength. Future researchers are encouraged to investigate the effects of educational interventions on foot care adherence among patients with Type 2 Diabetes Mellitus.